Concern for status among educated women - Bhushan, L. I.; Prasad, Rambha (New Delhi : Classical Pub. Co., 1993)
Study conducted in Munger City in Munger District, Bihar.
Includes bibliographical references (p. [124]-144).
Mimosa
Keywords: Feminism and education -- India -- Munger; Women in education -- India -- Munger; Women -- India -- Munger -- Social conditions